Effect of storage period and temperature on resistant starch and β-glucan content in cornbread - Niba, Lorraine L. (Food chemistry, 2003)
The objective of this study was to assess resistant starch development and β-glucan availability, as influenced by storage time and temperature. Cornbread was baked and freeze dried at −20 °C either whole or with the crust removed (crumb). Samples were stored in airtight containers at either 20 °C, 4 °C or −20 °C, for 2, 4 or 7 days, and analysed for resistant starch, β-glucans and starch damage. Resistant starch content in whole cornbread was 3.07 g/100 g [dry weight basis (dwb)] and 2.59 g/100 g (dwb) in the crumb. These levels increased with up to 4 days of storage, particularly at 4 °C. There was a decrease in resistant starch levels after 7 days of storage, with lowest levels at −20 °C. β-Glucan levels increased with storage. Starch damage percentage decreased with storage up to 4 days. These changes may be due to structural modification of components during storage.